2022
DOI: 10.33050/atm.v6i1.1638
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Employee Performance with Work Motivation as an Intervening Variable at the Semarang City Search and Rescue Office

Abstract: Employees are the main key in increasing productivity and the success of agency activities. Employees have an important role in reducing or minimizing the impact of loss or damage caused by a disaster. This study aims to analyse and empirically test the influence of leadership on employee work motivation, organizational culture on employee work motivation, leadership on employee performance, organizational culture on employee performance, work motivation on employee performance, work motivation in mediating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Several researchers have discovered a moderate correlation between these variables, lending credence to these striking findings: (Hajiali et al, 2022;Setyowati and Sofingi, 2022;Nasution and Priangkatara, 2022).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Several researchers have discovered a moderate correlation between these variables, lending credence to these striking findings: (Hajiali et al, 2022;Setyowati and Sofingi, 2022;Nasution and Priangkatara, 2022).…”
Section: Discussionmentioning
confidence: 89%
“…Hajiali et al (2022) also found that there is a positive relationship between all components of job performance and work motivation. The findings of a study by Setyowati and Sofingi (2022), who conducted a study among employees at the SAR Department of Semarang City, found that there is a positive relationship between motivation and job performance. Thus, it is proposed that Hypothesis 1 (H1): Work motivation is positively related to teachers' job satisfaction.…”
Section: The Relationship Between Work Motivation and Job Performancementioning
confidence: 99%
“…Recognizing the critical role of time management in fostering productivity and well-being, this paper proposes a structural framework designed to enhance time management proficiency within dynamic work settings [7]. Drawing upon established theories, empirical research, and practical insights, the framework inte-grates a range of strategies and techniques aimed at optimizing time allocation, enhancing task efficiency, and promoting proactive decision-making.…”
Section: Aptisi Transactions On Management (Atm) 153 ❒mentioning
confidence: 99%
“…Web administrations can be viewed as specialists because of their independence and heterogeneity. Proposed a multi-specialist framework that joins administrations due to competition between administrations [54].…”
Section: Ai-driven Approachmentioning
confidence: 99%